Catalyst as well as preparation method and application thereof

By doping chromium and manganese into the ruthenium oxide matrix and combining the coordination and dispersion of the chelating agent structure, an acidic OER catalyst with high activity and long-term stability was prepared, which solved the problem of poor stability of existing catalysts under industrial-grade conditions and achieved efficient and long-term stable operation of the catalyst.

CN119900046APending Publication Date: 2025-04-29DONGHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311412072.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2025-04-29

AI Technical Summary

Technical Problem

The existing acidic OER catalysts have poor long-term stability under industrial-grade high current conditions and cannot meet the performance requirements of commercial PEM systems for catalysts.

Method used

A catalyst was developed to prepare a catalyst with better uniformity by doping chromium and manganese into the ruthenium oxide matrix, combining the coordination and dispersion of the chelating agent structure, and to improve its stability through calcination treatment.

Benefits of technology

The catalyst has high activity and long-term stability under the acid electrolyte system, and the service period can reach 2000 hours, solving the problems of few types, low performance and poor stability of existing catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119900046A_ABST
    Figure CN119900046A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst and a preparation method and application thereof. According to the catalyst provided by the invention, the chromium and manganese double-doped ruthenium-based catalyst is utilized, and the coordination dispersion effect of a chelating agent structure is combined, so that sintering agglomeration of chromium, manganese and ruthenium components is effectively inhibited, and the prepared catalyst is better in uniformity; chromium and manganese regulate and control a d electron center of a ruthenium active site at the same time and serve as a high-corrosion resistance protective layer, and when an OER reaction is carried out in a strong acid electrolyte system, the catalyst can effectively keep the high activity characteristic and achieve long-period stable operation, and the service cycle can reach 2000 hours; the catalyst can be used as a high-performance acidic oxygen evolution reaction electrocatalyst, can be used for stably and efficiently carrying out oxygen evolution reaction (OER) in an acidic electrolyte environment, can be used as an anode material for hydrogen production by electrolysis of water, is used in a proton-conducting polymer electrolytic hydrogen production electrolytic tank, and solves the problems of few types, low performance and short service life of the existing acidic oxygen evolution catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of new energy, and in particular to a catalyst and a preparation method and application thereof. Background Art

[0002] Energy problems and environmental problems caused by the overexploitation of natural fossil fuels are two major challenges facing the world today. The growing demand for sustainable energy and serious ecological damage urgently require people to find sustainable clean energy. Hydrogen is an environmentally friendly, high-calorific value gaseous fuel. It is considered to be an ideal energy storage carrier for renewable energy and one of the most important fossil fuel substitutes in the future. Water electrolysis technology is currently an ideal technology for hydrogen production. Among the many water electrolysis technologies, proton exchange membrane (PEM) water electrolysis technology is one of the most promising technologies. However, the electrocatalytic oxygen evolution reaction (OER) in water electrolysis hydrogen production technology has a high reaction barrier and slow reaction kinetics, which has become the core bottleneck of water electrolysis hydrogen production reaction. Therefore, it is of great practical significance to develop highly active acidic OER catalysts to reduce the OER reaction barrier and increase the reaction rate. IrO x Due to its excellent acid stability, it is currently widely used as an acidic OER catalyst in commercial PEM systems. However, it is expensive and its reaction performance is still not ideal. Therefore, it is necessary to develop acidic stable OER catalytic materials with higher catalytic performance to replace the highly scarce Ir-based catalysts. At present, Ru-based catalytic materials with high acidic OER catalytic activity have received widespread attention, but the performance stability of Ru-based catalytic materials in acidic systems is still challenged. At present, researchers generally modify RuO2 catalytic materials by means of component structure regulation and electronic structure regulation to cope with the above challenges. The currently commonly used transition metal doping method, such as the use of single transition metals such as Mn, Ni, Cr to regulate the composition and electronic structure of RuO2 nanomaterials, can promote the catalytic activity or stability to a certain extent, but it still cannot effectively take into account both catalytic activity and stability. Especially under industrial-grade high current conditions, the long-term stability of related materials still cannot meet the performance requirements of commercial PEM systems for acidic OER catalysts. Therefore, developing acidic OER catalysts with both high activity and excellent stability remains a daunting challenge. Summary of the invention

[0003] The object of the present invention is to provide a catalyst.

[0004] Another object of the present invention is to provide a method for preparing the catalyst.

[0005] Another object of the present invention is to provide use of the above catalyst.

[0006] In order to solve the above technical problems, the first aspect of the present invention provides a catalyst, which includes a ruthenium oxide matrix and a transition metal element doped at the interface of the matrix, wherein the transition metal element includes chromium and manganese.

[0007] In some preferred embodiments, the transition metal element also includes ruthenium.

[0008] In some preferred embodiments, the molar ratio of the transition metal element doped at the interface of the substrate is: chromium: manganese: ruthenium = 1-2:1-2:7, for example 1:2:7.

[0009] In some preferred embodiments, the method for preparing the catalyst comprises the steps of:

[0010] S1, adding chromium salt, manganese salt and ruthenium salt to a liquid medium containing a chelating agent, stirring and reacting to obtain a reaction solution;

[0011] S2, centrifuging the reaction solution obtained in step S1 to remove the liquid, and then freeze-drying to obtain a solid;

[0012] S3, calcining the solid obtained in step S2 to obtain the catalyst.

[0013] The second aspect of the present invention provides a method for preparing a catalyst, the method comprising the steps of:

[0014] S1, adding chromium salt, manganese salt and ruthenium salt to a liquid medium containing a chelating agent, stirring and reacting to obtain a reaction solution;

[0015] S2, centrifuging the reaction solution obtained in step S1 to remove the liquid, and then freeze-drying to obtain a solid;

[0016] S3, calcining the solid obtained in step S2 to obtain the catalyst.

[0017] In some preferred embodiments, in step S1, the chelating agent is tannic acid.

[0018] In some preferred embodiments, in step S1, the liquid medium includes a solvent and aqueous ammonia dissolved in the solvent.

[0019] In some preferred embodiments, the solvent includes water and alcohol, preferably water and ethanol.

[0020] In some preferred embodiments, in the solvent, the volume ratio of the water to the ethanol is 4-5:1.

[0021] In some preferred embodiments, in step S1, the liquid medium includes water, ethanol and aqueous ammonia, and the volume ratio of water, ethanol and aqueous ammonia is 4-5:1:0.04-0.06, for example, 4.6:1:0.05.

[0022] In some preferred embodiments, the molar ratio of tannic acid, chromium salt, manganese salt and ruthenium salt is 0.002-0.003:1-2:1-2:7, for example 0.0029:1:2:7.

[0023] In some preferred embodiments, in step S1, the stirring reaction time is not less than 10 hours, more preferably not less than 20 hours, more preferably not less than 24 hours, more preferably not less than 48 hours, for example 24-48 hours.

[0024] In some preferred embodiments, in step S1, the stirring reaction temperature is room temperature, such as 24-28°C.

[0025] In some preferred embodiments, in step S2, the freeze-drying time is not less than 10 hours, more preferably not less than 16 hours, more preferably not less than 20 hours, for example 24 hours.

[0026] In some preferred embodiments, in step S3, the calcination treatment is performed in a muffle furnace.

[0027] In some preferred embodiments, in step S3, the calcination temperature is 200-800°C, more preferably 300-600°C, such as 400-550°C.

[0028] In some preferred embodiments, in step S3, the calcination treatment time is not less than 1 hour, more preferably not less than 2 hours, more preferably not less than 3 hours, for example 4 hours.

[0029] In some preferred embodiments, in step S3, the calcination treatment time is no more than 12 hours, more preferably no more than 10 hours, and more preferably no more than 5 hours.

[0030] The third aspect of the present invention provides the use of the catalyst provided in the first aspect of the present invention as an anode material for acidic water electrolysis.

[0031] According to a fourth aspect of the present invention, an electrolysis device is provided, comprising an electrolysis chamber, wherein the electrolysis chamber comprises a cathode, a cathode material, a diaphragm, an anode material, and an anode arranged in sequence, wherein the anode material comprises the catalyst described in the first aspect of the present invention.

[0032] In some preferred embodiments, the anode material is the catalyst described in the second aspect of the present invention.

[0033] In some preferred embodiments, the anode material is coated on a side of the separator close to the anode.

[0034] In some preferred embodiments, the anode material is coated on a side of the anode close to the separator.

[0035] In some preferred embodiments, the anode material is disposed between the anode and the separator.

[0036] A fifth aspect of the present invention provides a method for preparing hydrogen, the method comprising the steps of:

[0037] The electrolysis device described in the fourth aspect of the present invention is used to electrolyze water and collect electrolysis products to obtain hydrogen.

[0038] Compared with the prior art, the present invention has at least the following advantages:

[0039] (1) The catalyst provided in the embodiment of the present invention utilizes a ruthenium-based catalyst doped with chromium and manganese, combined with the coordination and dispersion effect of the chelating agent structure, to effectively inhibit the sintering and agglomeration of chromium, manganese and ruthenium components, and the prepared catalyst has better uniformity;

[0040] (2) In the catalyst provided in the embodiment of the present invention, chromium and manganese simultaneously regulate the d electron center of the ruthenium active site and act as a highly corrosion-resistant protective layer. When the OER reaction is carried out in a strongly acidic electrolyte system, the catalyst can effectively maintain its high activity characteristics and achieve long-term stable operation, with a service life of up to 2000 hours;

[0041] (3) The catalyst provided in the embodiment of the present invention achieves the effective synthesis of highly crystalline ultrafine nanoparticle structure by regulating the nanometer size of ruthenium oxide doped with chromium and manganese;

[0042] (4) The catalyst provided in the embodiments of the present invention, as a high-performance acidic oxygen evolution reaction electrocatalyst, can stably and efficiently carry out oxygen evolution reaction (OER) in an acidic electrolyte environment, and can be used as an anode material for hydrogen production by electrolysis of water, and can be used in a proton-conducting polymer electrolysis hydrogen production electrolytic cell, thereby solving the problems of the existing acidic oxygen evolution catalysts having few types, low performance, and short service life.

[0043] It should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described below (such as embodiments) can be combined with each other to form a new or preferred technical solution. Due to space limitations, they will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] One or more embodiments are exemplarily described by the pictures in the corresponding drawings, and these exemplary descriptions do not constitute limitations on the embodiments.

[0045] Figure 1It is the X-ray diffraction pattern of the Ru@CrMn-RuO2 catalyst described in the embodiments and comparative examples of the present invention. Since the XRD patterns of the samples are relatively similar, sample 2# is used as a representative to compare RuO2 and other metal-doped RuO2.

[0046] Figure 2 This is the result obtained from the oxygen evolution polarization curve of the Ru@CrMn-RuO2 catalyst described in Example 2 of the present invention, where the (left) figure is the oxygen evolution polarization curve of samples of Examples 1, 3, 4, 5, and 6, and the sample obtained from Example 2 with the best performance is shown in (right).

[0047] Figure 3 This is a scanning electron microscope image of the Ru@CrMn-RuO2 catalyst in Example 2 of the present invention.

[0048] Figure 4 This is a transmission electron microscope image of the Ru@CrMn-RuO2 catalyst in Example 2 of the present invention.

[0049] Figure 5 The Ru@CrMn-RuO2 catalyst in Example 2 of the present invention is subjected to a current density of 100 mA cm -2 Below, long-term stability test results. DETAILED DESCRIPTION

[0050] Existing acidic OER catalysts cannot effectively balance catalytic activity and stability. Especially under industrial-grade high current conditions, the long-term stability of related materials is poor, and they will be deactivated in a dozen or dozens of hours. The slightly better stability has poor activity and cannot meet the performance requirements of commercial PEM systems for acidic OER catalysts. After extensive and in-depth research, the inventors have developed an acidic OER catalyst that has both high activity and excellent stability and is suitable for promotion and application.

[0051] catalyst

[0052] The present invention relates to a catalyst comprising a ruthenium oxide matrix and transition metal elements doped on the interface of the ruthenium oxide matrix, wherein the transition metal elements include chromium and manganese. Doping herein means that the elements can be uniformly coated on the interface in any existing form. Preferably, the elements are uniformly doped on the interface in the form of their oxides or simple substances.

[0053] In some more preferred embodiments of the present invention, the transition metal element further comprises ruthenium, and in this case, chromium, manganese and ruthenium are doped on the interface in any existing form. Preferably, the molar ratio of the transition metal element doped on the matrix interface is chromium: manganese: ruthenium = 1-2: 1-2: 7. For example, 1:2:7.

[0054] Preparation method

[0055] The present invention also relates to a method for preparing a catalyst, comprising the following steps: S1, adding a chromium salt, a manganese salt and a ruthenium salt to a liquid medium containing a chelating agent, stirring and reacting to obtain a reaction liquid; S2, centrifuging the reaction liquid obtained in step S1 to remove the liquid, and then freeze-drying to obtain a solid; S3, calcining the solid obtained in step S2 to obtain a catalyst.

[0056] In the above step S1, the liquid medium includes a solvent and ammonia water dissolved in the solvent. The solvent includes water and alcohol, preferably water and ethanol. When the liquid medium is water and ethanol, the volume ratio of water to ethanol is preferably 4-5:1. In the liquid medium, ammonia water provides a suitable pH value, and when the volume ratio of water, ethanol and ammonia water is 4-5:1:0.04-0.06, the pH value obtained is considered to be suitable.

[0057] Tannic acid is preferably used as the chelating agent. Tannic acid cooperates with various transition metal elements in a suitable liquid medium to form a nanoparticle crystal structure. The amount of tannic acid used is preferably determined according to the molar amount of each transition metal element. Preferably, the molar ratio of tannic acid, chromium salt, manganese salt and ruthenium salt is 0.002-0.003:1-2:1-2:7, for example 0.0029:1:2:7.

[0058] The reaction time of the stirring reaction in step S1 is not less than 10 hours, more preferably not less than 20 hours, more preferably not less than 24 hours, for example 24-48 hours. A reaction time of more than 24 hours can allow for a more complete reaction and a more uniform catalyst. The reaction temperature of the stirring reaction in step S1 can be room temperature, for example 24-28°C.

[0059] In the above step S2, the reaction solution obtained in step S1 is taken and the liquid is removed. The step of removing the liquid is preferably centrifugation, and can also be filtration. The freeze-drying step further removes the liquid to obtain a solid.

[0060] In the above step S3, the solid obtained in step S2 is subjected to calcination treatment, and the calcination treatment can be carried out in any equipment that provides high temperature, such as a muffle furnace. The temperature of the calcination treatment is 200-800°C, more preferably 300-600°C, for example 400-550°C. The temperature of the calcination treatment here affects the performance of the obtained catalyst. For example, when the temperature of the calcination treatment is 400-550°C, the obtained catalyst activity is better. Optimally, when the temperature of the calcination treatment is 450°C, the obtained catalyst activity is the best. As the time for the calcination treatment, it is not less than 1 hour, more preferably not less than 2 hours, more preferably not less than 3 hours, for example 4 hours. And the time is not higher than 12 hours, more preferably not higher than 10 hours, more preferably not higher than 5 hours. Preferably it is 4-5 hours.

[0061] use

[0062] The invention also relates to the use of the catalyst as an anode material of a device used in acidic water electrolysis.

[0063] As used in the present invention, the term "anode material" refers to an anode catalytic material, and in an embodiment of the present invention, refers to the catalyst of the present invention.

[0064] Electrolysis device

[0065] The present invention also relates to an electrolysis device, which is used for acidic electrolysis of water, and the device includes an electrolysis chamber, and the electrolysis chamber includes a fourth aspect of the present invention, which provides an electrolysis device, the electrolysis device includes an electrolysis chamber, and the electrolysis chamber includes a cathode, a cathode material, a diaphragm, an anode material, and an anode arranged in sequence, and the anode material includes the catalyst described in the first aspect of the present invention. Preferably, the anode material is arranged between the anode and the diaphragm, for example, the anode material is preferably coated on the side of the diaphragm close to the anode, or the anode material is coated on the side of the anode close to the diaphragm, or the anode material is formed separately and located between the anode and the diaphragm.

[0066] The connection method and application principle of the cathode, anode and diaphragm of the electrolysis device of the present invention belong to conventional technical means in the field, and other parts of the electrolysis device of the present invention can refer to commercially available acidic water electrolysis devices and conventional methods in the field.

[0067] Method for producing hydrogen

[0068] The present invention also relates to a method for preparing hydrogen, comprising the steps of: using the above electrolysis device to electrolyze water, and collecting electrolysis products to obtain hydrogen.

[0069] To make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the present invention is further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, percentages and parts are weight percentages and weight parts. The experimental materials and reagents used in the following examples can be obtained from commercial channels unless otherwise specified.

[0070] Unless otherwise specified, the technical and scientific terms used herein have the same meaning as commonly understood by ordinary technicians in the technical field to which the application belongs. It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments of the application.

[0071] Unless otherwise indicated, the term "or" means and is used interchangeably with the term "and / or".

[0072] As used herein, including the appended claims, singular forms of words such as "a," "an," and "the" include their corresponding plural referents unless the context clearly dictates otherwise.

[0073] Example 1

[0074] 0.4 ml of ammonia water and 0.2 g of tannic acid were added to a mixture of 37 ml of water and 8 ml of ethanol and mixed evenly. 0.04 mol of chromium nitrate, 0.08 mol of manganese nitrate and 0.28 mol of ruthenium chloride were added to the mixed solution, stirred at room temperature for 24 h, centrifuged and freeze-dried for 12 h to obtain a solid product A.

[0075] The obtained solid product A was placed in a muffle furnace at 550° C. in an air atmosphere for 4 h to obtain catalyst sample 1#.

[0076] Example 2

[0077] 0.4 ml of ammonia water and 0.2 g of tannic acid were added to a mixture of 37 ml of water and 8 ml of ethanol and mixed evenly. 0.04 mol of chromium nitrate, 0.08 mol of manganese nitrate and 0.28 mol of ruthenium chloride were added to the mixed solution, stirred at room temperature for 48 h, centrifuged and freeze-dried for 24 h to obtain a solid product A.

[0078] The obtained solid product A was placed in a muffle furnace at 450° C. in an air atmosphere for 4 h to obtain catalyst sample 2#.

[0079] Example 3

[0080] 0.4 ml of ammonia water and 0.2 g of tannic acid were added to a mixture of 37 ml of water and 8 ml of ethanol and mixed evenly. 0.04 mol of chromium nitrate, 0.08 mol of manganese nitrate and 0.28 mol of ruthenium chloride were added to the mixed solution, stirred at room temperature for 48 h, centrifuged and freeze-dried for 24 h to obtain a solid product A.

[0081] The obtained solid product A was placed in a muffle furnace at 400° C. in an air atmosphere for 4 h to obtain catalyst sample 3#.

[0082] Example 4

[0083] 0.4 ml of ammonia water and 0.2 g of tannic acid were added to a mixture of 37 ml of water and 8 ml of ethanol and mixed evenly. 0.04 mol of chromium nitrate, 0.08 mol of manganese nitrate and 0.28 mol of ruthenium chloride were added to the mixed solution, stirred at room temperature for 24 h, then hydrothermal at 100 ° C for 12 h, centrifuged and freeze-dried for 24 h to obtain solid product A.

[0084] The obtained solid product A was placed in a muffle furnace at 400° C. in an air atmosphere for 4 h to obtain catalyst sample 4#.

[0085] Example 5

[0086] 0.4 ml of ammonia water and 0.2 g of tannic acid were added to a mixture of 37 ml of water and 8 ml of ethanol and mixed evenly. 0.04 mol of chromium nitrate, 0.08 mol of manganese nitrate and 0.28 mol of ruthenium chloride were added to the mixed solution, stirred at room temperature for 24 h, centrifuged and freeze-dried for 12 h to obtain a solid product A.

[0087] The obtained solid product A was placed in a muffle furnace at 450° C. in an air atmosphere for 3 h to obtain catalyst sample 5#.

[0088] Example 6

[0089] 0.4 ml of ammonia water and 0.2 g of tannic acid were added to a mixture of 37 ml of water and 8 ml of ethanol, and the mixture was mixed evenly. 0.04 mol of chromium nitrate, 0.08 mol of manganese nitrate, and 0.28 mol of ruthenium chloride were added to the mixed solution, stirred at room temperature for 24 h, centrifuged, and freeze-dried for 24 h to obtain a solid product A.

[0090] The obtained solid product A was placed in a muffle furnace at 500° C. in an air atmosphere for 4 h to obtain catalyst sample 6#.

[0091] The catalyst sample 1-6# obtained in Example 1-6 was subjected to X-ray diffraction test, and the test results are shown in Figure 1 The obtained samples 1#-6# are dominated by diffraction peaks of Ru and RuO2, and no peaks of Mn, Cr and their oxides are detected, indicating that the catalyst samples are mainly composed of Ru and RuO2, and Mn and Cr are highly dispersed.

[0092] The catalyst samples obtained in Examples 1-6 were tested for oxygen evolution catalytic activity in a 1M HClO4 aqueous solution. The results are shown in Figure 2 .Depend on Figure 2 It can be seen that the catalyst sample stirred for 48 h, freeze-dried for 24 h, and kept at 450 °C for 4 h showed excellent OER performance, 100 mA cm -2 The overpotential is only 226mV, which is better than RuO2 and other metal-doped RuO2 catalysts.

[0093] The catalyst sample obtained in Example 2 was tested by scanning electron microscope. The test results are shown in Figure 3 .Depend on Figure 3 It can be seen that the catalyst is a nanoparticle structure. The nanoscale particle size gives the catalyst an extremely high surface utilization rate, so it has performance advantages compared to catalysts of other morphologies.

[0094] The catalyst sample 2# obtained in Example 2 was tested by transmission electron microscopy. The test results are shown in Figure 4 .Depend on Figure 4 It can be seen that the catalyst presents a coated core-shell structure, which can well protect the active Ru inside, making it difficult to dissolve during the reaction, thereby enabling the catalytic process to operate efficiently and stably for a long time.

[0095] The catalyst sample obtained in Example 2 was subjected to a constant current acidic oxygen evolution stability test. The test results are shown in Figure 5 .Depend on Figure 5 It can be seen that sample 2# can effectively carry out OER reaction in 1.0M HClO4 for more than 2000h without significant performance degradation, which is much higher than the performance of most catalysts. This fully proves the long-term stability of the catalytic performance of this sample.

[0096] In summary, the present invention provides a preparation and application of a high-performance oxygen evolution catalyst suitable for high-strength acid electrolytes. The prepared Ru@CrMn-RuO2 catalyst can be used as an anode material for an acidic water electrolysis hydrogen production electrolytic cell, solving the problem of few types, low activity and poor stability of existing acidic OER catalysts. The prepared Ru@CrMn-RuO2 catalyst exhibits excellent oxygen evolution activity and long-term stability in acidic media, which is far superior to most of the related catalysts reported. Therefore, the present invention effectively overcomes the seed shortcomings of the prior art and has high commercial value.

[0097] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present invention, and in actual applications, various changes may be made thereto in form and detail without departing from the spirit and scope of the present invention.

Claims

1. A catalyst, characterized in that The catalyst comprises a ruthenium oxide-based matrix and a transition metal element doped on the interface of the matrix, wherein the transition metal element comprises chromium and manganese.

2. The catalyst according to claim 1, characterized in that The transition metal element also includes ruthenium.

3. The catalyst according to claim 2, characterized in that The molar ratio of the transition metal elements doped on the interface of the substrate is: chromium: manganese: ruthenium = 1-2:1-2:

7.

4. The method for preparing a catalyst according to any one of claims 1 to 3, characterized in that: The method comprises the steps of: S1, adding chromium salt, manganese salt and ruthenium salt to a liquid medium containing a chelating agent, stirring and reacting to obtain a reaction solution; S2, centrifuging the reaction solution obtained in step S1 to remove the liquid, and then freeze-drying to obtain a solid; S3, calcining the solid obtained in step S2 to obtain the catalyst.

5. The catalyst according to claim 4, characterized in that In step S1, the chelating agent is tannic acid; and / or, the liquid medium comprises a solvent and aqueous ammonia dissolved in the solvent; and / or, the molar ratio of the tannic acid, the chromium salt, the manganese salt and the ruthenium salt is 0.002-0.003:1-2:1-2:7; And / or, the stirring reaction time is not less than 10 hours; And / or, the temperature of the stirring reaction is room temperature.

6. The catalyst according to claim 4, characterized in that The liquid medium includes water, ethanol and ammonia water, and the volume ratio of water, ethanol and ammonia water is 4-5:1:0.04-0.

06.

7. The catalyst according to claim 4, characterized in that In step S2, the freeze-drying time is not less than 10 hours; And / or, in step S3, the calcination treatment is carried out in a muffle furnace; And / or, the calcination temperature is 200-800°C; And / or, the calcination time is not less than 1 hour, and the calcination time is not more than 12 hours.

8. Use of the catalyst according to any one of claims 1 to 3 as an anode material for acidic water electrolysis.

9. An electrolysis device, characterized in that: The electrolysis device comprises an electrolysis chamber, wherein the electrolysis chamber comprises a cathode chamber having a cathode, an anode chamber having an anode, and a diaphragm located between the cathode chamber and the anode chamber, wherein the anode comprises the catalyst according to the first aspect of the present invention.

10. A method for preparing hydrogen, characterized in that: The method comprises the steps of: The electrolysis device described in claim 9 is used to electrolyze water and collect electrolysis products to obtain hydrogen.